The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/5939372
|View full text |Cite
|
Sign up to set email alerts
|

Association between Alanine Aminotransferase and Growth Hormone: A Retrospective Cohort Study of Short Children and Adolescents

Abstract: Objective. This study aimed to examine the relationship between serum alanine aminotransferase (ALT) and growth hormone (GH) in children and adolescents with short stature. Methods. In this retrospective cohort study, 670 Chinese children and adolescents with short stature were included, and 253 of them received recombinant human GH (rhGH) therapy. Anthropometric and biochemical indicators were measured. GH peak levels were assessed after provocation tests with L-dopa and insulin. The subjects were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…In addition, a negative correlation was found between GH peak and ALT in subjects with GH peak <5 ng/mL. This nding is consistent with reports by Ji et al, who found that the GH secretion levels in children and adolescents with short stature were signi cantly and negatively correlated with ALT and that recombinant human growth hormone (rhGH) therapy reduced ALT levels [22] .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a negative correlation was found between GH peak and ALT in subjects with GH peak <5 ng/mL. This nding is consistent with reports by Ji et al, who found that the GH secretion levels in children and adolescents with short stature were signi cantly and negatively correlated with ALT and that recombinant human growth hormone (rhGH) therapy reduced ALT levels [22] .…”
Section: Discussionsupporting
confidence: 90%
“…Skin diseases have been broadly described in postmenopausal women and correlate with letrozole‐induced changes in sex hormone levels 37 . Abnormal liver function has been observed in GH monotherapy patients; in the boy from this study, letrozole treatment was stopped, but he continued on GH after 15 days; liver function return to normal 38 . In prior studies, HDL‐C reductions within the normal range have been observed; here, four boys had HDL‐C reductions below the limit of 1.04 mmol/L 12 …”
Section: Discussionmentioning
confidence: 50%
“…37 Abnormal liver function has been observed in GH monotherapy patients; in the boy from this study, letrozole treatment was stopped, but he continued on GH after 15 days; liver function return to normal. 38 In prior studies, HDL-C reductions within the normal range have been observed; here, four boys had HDL-C reductions below the limit of 1.04 mmol/L. 12 ADRs should be closely monitored during letrozole therapy in Chinese pubertal boys.…”
Section: Discussionmentioning
confidence: 67%
“…Few studies have evaluated the presence of NAFLD in GHD children due to the very low prevalence of NAFLD in young children. A recent study reported a negative association between PGH level and ALT level in short children and adolescents without NAFLD [36].…”
Section: A B Cmentioning
confidence: 94%